Preparation of Conjugated Polymer Dots as a Fluorescence Turn-On Assay for Bovine Serum Albumin by Interaction with Graphene Oxide - Noh, Jaeguk; Son, Sangho; Kim, Yongkyun; Chae, Byung-Jae; Ku, Bon-Cheol; Lee, Taek Seung (TAYLOR & FRANCIS LTD, 2014)
Fluorescent conjugated polymers with various monomer compositions were synthesized via Suzuki coupling polymerization and spherically-shaped conjugated polymer dots (CPdot) with uniform size were prepared via conventional reprecipitation technique. Chemically modified graphene oxide (GO) was prepared to use as a component of sensor platform for protein detection. GO showed an excellent interaction with CPdot on its surface via hydrophobic interaction, which, in turn, induced the quenching of the fluorescence of CPdot. Upon exposure to bovine serum albumin (BSA), the quenched fluorescence was recovered, resulting from the release of CPdot from the complex with GO, as BSA adsorbed preferentially on the GO surface.
Keywords: CYSTEINE DETECTION; CHEMICAL SENSORS; NANOPARTICLES; NANOSTRUCTURES; COMPLEX; CARBON; DNA